Disclosure of Carbon Emissions, Covid-19, Green Innovations, Financial Performance, and Firm Value - Prasetyo Ramadhan; Puspita Rani; Endah Sri Wahyuni (Institute of Research and Community Outreach - Petra Christian University, 2023)
The purpose of this study is to investigate the effect of the publication of carbon emissions, COVID-19, and green innovation on financial overall performance and their impact on firm value. The population utilized here are Indonesian companies registered at the Indonesia Stock Exchange from 2015 to 2021 acquired from forty-eight organizations as a sample using purposive sampling. Path analysis is used as the analysis method. This study found that the publication of carbon emissions had no enormous impact on financial performance, while COVID-19 had a full-size negative impact on financial overall performance and green innovation had a substantial-higher-quality impact on financial performance. Meanwhile, COVID-19 has an extensive negative impact on firm value, financial performance has a substantial effect on firm value, and disclosure of carbon emissions and green innovation has no massive effect on firm value. Similarly, financial performance cannot seriously mediate the effect of carbon emission disclosure on firm value. However, financial performance was capable of noticeably mediating the bad effect of COVID-19 on firm value and the big high effect of green innovation on firm value.